1994
DOI: 10.1190/1.1443665
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of the magnetic anomaly over the Omaha Oil Field, Gallatin County, Illinois

Abstract: A 40 nanoTesla (nT) magnetic anomaly identified in an aeromagnetic survey over southern Illinois contours as a localized magnetic high on the west flank of a regional magnetic low. This magnetic anomaly is generally coincident with the Omaha Oil Field in northwest Gallatin County, Illinois. It was initially assumed that cultural sources of steel associated with this oil field were the primary source of the magnetic feature; however, similar oil fields overflown by the survey do not exhibit magnetic anomalies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…For example, Krassay et al (2013) demonstrated the utility of forward magnetic anomaly modeling of interpreted mafic igneous sills or tabular intrusions within sedimentary basins when high-resolution magnetic intensity data and a coincident grid or network of seismic profiles are available. In the southern Illinois Basin, occasional positive magnetic anomalies have been shown to be related to shallow ultramafic igneous sills intruded into Paleozoic sediments by forward modeling of high-resolution magnetic intensity data (Sparlin and Lewis, 1994). In both of these cases, the sills or series of sills, which individually ranged in thickness from 72 m to a few hundred meters, produced magnetic anomalies of 100-250 nT.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Krassay et al (2013) demonstrated the utility of forward magnetic anomaly modeling of interpreted mafic igneous sills or tabular intrusions within sedimentary basins when high-resolution magnetic intensity data and a coincident grid or network of seismic profiles are available. In the southern Illinois Basin, occasional positive magnetic anomalies have been shown to be related to shallow ultramafic igneous sills intruded into Paleozoic sediments by forward modeling of high-resolution magnetic intensity data (Sparlin and Lewis, 1994). In both of these cases, the sills or series of sills, which individually ranged in thickness from 72 m to a few hundred meters, produced magnetic anomalies of 100-250 nT.…”
Section: Discussionmentioning
confidence: 99%
“…Mafic sills are occasionally penetrated in drillholes in the surrounding area of the U.S. midcontinent (e.g., Lucius and Von Frese, 1988;Wickstrom etaL, 1992) with ages of 1.3-1.0 Ga, and ultramafic dikes of Permian age crop out or are exposed in coal mines in southern Illinois 10-20 km south of the seismic profile (Clegg and Bradbury, 1956). The "Omaha Dome," located several kilometers south of the seismic profile, is an uplift caused by the intrusion of ultramafic sills or laccoliths into the Upper Devonian New Albany Group and younger strata (for review, see Nelson, 1995); however, deeper units appear to be unaffected by intrusion (Stevenson et al, 1981), an observation supported by magnetic anomaly modeling (Sparlin and Lewis, 1994). Gravity anomaly and residual magnetic intensity maps Hildenbrand and Kucks, 1993) indicate a steep, NE-trending gradient crossing the profle in the vicinity of the dipping reflector zone that bounds a negative gravity and magnetic anomaly to the southeast.…”
Section: Discussionmentioning
confidence: 92%
“…The fault system of the rift is exposed as the Fluorspar Area Fault Complex of western Kentucky and southeastern Illinois (Figure 3). There, alkaline ultramafic dikes, sills, and complexes of Permian age are abundant, many having intruded along short, northwest-striking cross faults that link longer, northeast-striking faults (see Figure 6; Zartman et al, 1967;Bikerman et al, 1982;Trace and Amos, 1984;Snee and Hayes, 1992;Sparlin and Lewis, 1994;Nelson, 1995;M.L. Sargent, written communs., 1995 andHildenbrand and Ravat, this volume).…”
Section: Igneous Rocksmentioning
confidence: 95%